Leading sensory modality in physical education for schoolchildren with disabilities - Vetrenko A.A. ,; Vetrenko S.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to investigate the leading modality of perception in schoolchildren with mental retardation and to develop methodological recommendations for organizing physical education classes, taking into account the leading type of perception of the students. Methods and structure of the study. 20 schoolchildren of early adolescence with mental retardation were examined at Secondary School No. 8 in Ishim, Tyumen Oblast. The experimental study used observation, the ‘Leading Modality’ methodology developed by the authors, the ‘Concept Exclusion’ and ‘Concept Relation’ thinking study methodologies, the Raven's test, and ‘Classification.’ Results and conclusions. The leading modalities of perception in adolescents with mental retardation have been identified, and a higher level of development of visual-figurative thinking than verbal-logical thinking has been established. The differences found are statistically significant. Student's t-test was used to assess the reliability of the differences. Methodological recommendations for organizing physical education classes taking into account the leading sensory modality of students were proposed.